2015
DOI: 10.1038/srep10437
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-497 and miR-663b in plasma are potential novel biomarkers for bladder cancer

Abstract: MicroRNAs (miRNAs), abundant and highly stable in the plasma, have been widely reported. This greatly pursued us to investigate whether plasma miRNAs could be considered as powerful biomarkers for diagnosing bladder cancer (BC). We performed a plasma miRNAs profile with the TaqMan Low Density Array, and a two-phase validation to detect the candidate miRNAs expression by quantitative PCR. The receiver operating characteristic curve (ROC) and the area under curve (AUC) were used to evaluate diagnostic accuracy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 41 publications
1
93
0
Order By: Relevance
“…[29] Only one study observed miR-455 significantly down-regulated in HCC tissue and serum in HCC related to type I glycogen storage disease. [30] The different up-regulation patterns of miR-130a and miR-505 in other solid tumors (bladder, [31] breast, [32] gastric, [33] ovarian, [34] colorectal [35] and non-small cell lung cancers [36] ) provide further evidence for their potential as HCC specific biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Only one study observed miR-455 significantly down-regulated in HCC tissue and serum in HCC related to type I glycogen storage disease. [30] The different up-regulation patterns of miR-130a and miR-505 in other solid tumors (bladder, [31] breast, [32] gastric, [33] ovarian, [34] colorectal [35] and non-small cell lung cancers [36] ) provide further evidence for their potential as HCC specific biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these notions, their participation in the TCC progression has been widely reported1819202122232425. For example, Jin et al .…”
Section: Discussionmentioning
confidence: 82%
“…MiR-99a-5p was significantly down-regulated in bladder cancer tissues, and the lower expression of miR-99a was correlated with the more aggressive phenotypes of bladder cancer. Moreover, miR-99a-5p was also decreased in plasma and urine supernatants of bladder cancer patients [24,26,27]. Besides the diagnostic value, miR99a-5p was a predictive marker of OS of bladder cancer by both of studies based on clinical samples and TCGA resource [17,28].…”
Section: Discussionmentioning
confidence: 85%
“…In cellular component and molecular function, the processes most strongly enriched were endomembrane system and transcription regulator activity relatively R [20][21][22][23]. Furthermore, miR-1-3p was reported to be decreased in the plasma of bladder cancer patients, as compared to healthy controls, which increased the chances for miR-1-3p to be a non-invasive biomarker for the early detection of bladder cancer [24]. The restoration of miR-1-3p in vitro could induce cell apoptosis in bladder cancer cell lines [20,25].…”
Section: Discussionmentioning
confidence: 99%